MORPHOMETRY OF EQUINE PLACENTA - SIVAKUMAR, A; KULASEKAR, K; DEVANATHAN, T G; RAMESH, GEETHA (The Indian Journal of Animal Reproduction, 2023)
The Growth and development of fetus is dependent upon placenta of individuals functional capabilities.In this study morphometry of placenta of fifty six thorough breed mares aged between 9 to 13 years werestudied after normal foaling in which the foals born were alive. The prototype of expulsion, gross morphology,morphometry, placental expulsion lime, and umbilical cord length was studied. All placenta were expelledwith the allantoic side (non-villous surface) of allantochorion outermost. The mean placental expulsion timewas 66.89± 3.90 min. The mean length of pregnant horn, non-pregnant horn, total body, posterior bodyand anterior body of pregnant horn were 63.49±0.81, 56.63±0.81, 132.64±0.98, 67.52± 1.11 and 107.93±1.02cm respectively. The umbilical cord length was 60.30±1.04cm. The mean weight of the total placenta was4.70±0.11kg. Morphometry of placenta can be used as a determinant of foals well being.
Keywords: Equine; Placenta; Morphometry